Milk price changes in Poland in the context of the Common Agricultural Policy - Piotr Borawski; Marta Guth; Wojciech Truszkowski; Dagmara Zuzek; Aneta Beldycka-Borawska; Bartosz Mickiewicz; Elzbieta Szymanska; Jayson Kennedy Harper; James William Dunn (Agricultural Economics (AGRICECON), 2020)
Changes in the retail prices of pasteurised milk, purchase prices, and the price relationship between retail prices for pasteurised milk and other food products are analysed for Poland during the period from 2004-2018. In addition, the paper presents factors affecting changes in milk prices in Poland and characterises the Common Agricultural Policy (CAP) on the milk market. The adoption of a long period of analysis allows for the study of periods of both high and low variability. The data analysis uses various methods including the Augmented Dickey-Fuller (ADF) test and the Autoregressive-Moving-Average Model (ARMA). The milk market showed significant response because it was one of the few that was strongly administered by the European Union. These policies led to a significant increase in milk prices in the analysed period. The average price of pasteurised food milk increased by 63% in 2003-2015, and the purchase farm price of milk increased by 91.74%. The situation changed when the production limits were eliminated after 2015. In the initial period after quotas ended, the price of milk decreased and then increased. Similar changes were observed in other EU countries. Even short-term fluctuations associated with economic crises did not significantly affect the milk market.